Molecular mapping of platelet hyperreactivity in diabetes: the stress proteins complex HSPA8/Hsp90/CSK2α and platelet aggregation in diabetic and normal platelets - Chiva-Blanch, Gemma; Peña, Esther; Cubedo, Judit; García-Arguinzonis, Maisa; Pané, Adriana; Gil, Pedro A; Perez, Antonio; Ortega, Emilio; Padró, Teresa; Badimon, Lina (Translational research : the journal of laboratory and clinical medicine, 2021)
The molecular understanding of the pathophysiological changes elicited by diabetes in platelets may help in further elucidating the involvement of this pseudo-cell in the increased risk of developing cardiovascular disease and thrombosis in diabetic subjects. We aimed to investigate the differential characteristics of platelets from diabetic patients and nondiabetic controls to unveil the molecular mechanisms behind the increased platelet reactivity in diabetes. We compared platelets from diabetic and control subjects by 2 dimensional-electrophoresis followed by mass spectrometry. Changes in selected differential proteins were validated by immunoprecipitation assays and western blot. Platelet aggregation was measured by light transmittance aggregometry induced by collagen and ADP, and dynamic coagulation analysis of whole blood was measured by thromboelastometry. We observed significant differences in proteins related to platelet aggregation, cell migration, and cell homeostasis. Subjects with diabetes showed higher platelet aggregation and thrombogenicity and higher contents of the stress-related protein complex HSPA8/Hsp90/CSK2α than nondiabetic subjects. Changes in the chaperones HSPA8 and Hsp90, and in CSK2α protein contents correlated with changes in platelet aggregation and blood coagulation activity. In conclusion, the complex HSPA8/Hsp90/CSK2α is involved in diabetes-related platelet hyperreactivity. The role of the HSPA8/Hsp90/CSK2α complex may become a molecular target for the development of future preventive and therapeutic strategies for platelet dysfunction associated with diabetes and its complications.